Foreign ownership and firm survival: First evidence for enterprises in Germany - Joachim Wagner; John Philipp Weche Gelübcke (Institute for the Study of Labor (IZA), 2011)
This paper documents the relationship between foreign ownership and firm survival for enterprises in Germany using unique tailor-made new representative data that merge information from surveys performed by the Statistical Offices, from administrative data collected by the Tax Authorities and from a commercial data provider. It contributes to the literature by providing the first evidence on the role of foreign ownership for firm survival in Germany, one of the most important destination countries for foreign direct investments. Our micro-econometric analysis reveals a ceteris paribus higher risk of exit for foreign owned firms in West Germany but not in East Germany.
urn:nbn:de:101:1-201201107564
Keywords: F23; L60; 330; foreign ownership; firm survival; Germany; Unternehmenserfolg; Eigentümerstruktur; Multinationales Unternehmen; Direktinvestition; Ausländisch; Schätzung; Deutschland